Peran Orang Tua dalam Menanamkan Sikap Disiplin pada Anak Usia 5-6 Tahun di Ra Ash-Sholihah Kecamatan Medan Johor - Dwi Nurjani; Khadijah Khadijah; Zulkipli Nasution (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
Talking about education cannot be separated from the family environment. A harmonious family life is built with a good interaction system, so that education in the family runs conducively. Parents are figures who serve as examples for their children. The good and bad of children in the future depends on the role of parents in educating them. This research aims to describe: 1) Parental programs in instilling discipline in early childhood. 2) Steps taken by parents in instilling discipline in young children. 3) Motivation of parents in instilling discipline in young children. This research uses qualitative research methods with a descriptive approach. to find out and describe the reality of the event being studied so as to make it easier to obtain objective data. Based on the results of research at RA Ash-Sholihah, Medan Johor District, parents gave appreciation as a form of motivation for children's disciplinary attitudes in implementing the rules made. Then provide motivation in the form of words of praise like a great child, giving appreciation in the form of awards or prizes.